Factors Creating Conflict in Small Traditional Medicine - Yuniariana Pertiwi; Kintoko; Suliyanto; Nursanti; Septiana Indratmoko (Postgraduate, University of Mataram, 2025)
Conflicts are widespread in everyday life, whether in the home, at work, or in traditional medicine. Conflicts in the field of traditional medicine can arise as a result of numerous disagreements about the use of raw materials, manufacturing methods, and marketing strategies for herbal medicine, the presence of inappropriate job desks, the occurrence of role conflicts, horizontal conflicts, and interpersonal conflicts between managers and herbal medicine entrepreneurs. Until a legal matter reached the courtroom, the largest feud in history had occurred. The goal of this study is to identify the variables that contribute to conflict, which can then be used to resolve the conflict controversy in the field of traditional medicine in Cilacap Regency. This is qualitative research using a case study methodology. This study's respondents were employees of Small Traditional Medicine Enterprises (UKOT) in Cilacap Regency. Researchers collected data directly from participants using a questionnaire and in-depth interviews. Nonprobability sampling and snowball sampling were utilized. The findings indicate that communication, disparities in personal values, discrepancies in perception, and rewards are the primary causes of conflict at UKOT in Cilacap.